Algorithm of prognosis of psychological adaptation-maladaptationas the basis of personalized psycho-correction of patients with dermatological diseases with different levels of vital threat - T. Abdryakhimova; G. Skrebtsova (Journal of Education, Health and Sport, 2023)
Purpose: to substantiate the algorithm for predicting the state of psychological adaptation - maladaptation of patients with dermatological pathology with different levels of vital threat, on the basis of which to develop personalized psychocorrection programs for this contingent, and to evaluate the effectiveness of their implementation. .